fast track: Analisa Faktor Pendukung dan Penghambat Pengambilan Keputusan Klinis Kasus Kompleks Dalam Kolaborasi Antarprofesi : A Literature Review - ardiani, dewi ulfah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
ABSTRACTBackground: Clinical decision-making in complex cases often encounters difficulties and obstacles in its implementation. The decisions made face various challenges, particularly in the context of Interprofessional Collaboration (IPC). Therefore, it is crucial to understand the factors influencing clinical decision-making in complex cases to improve the quality of care, especially within the framework of interprofessional collaboration.Objective: To identify and analyze the most dominant facilitating and inhibiting factors in clinical decision-making for complex cases through an interprofessional collaboration approach, as well as to explore existing research gaps.Method: This literature review integrates findings from eleven articles focusing on the dynamics of IPC in clinical decision-making for complex cases. The analysis was conducted to identify key themes related to the facilitating and inhibiting factors of clinical decision-making in IPC. Results: Three primary facilitating factors identified in this study include effective and open communication, patient-centered care, and collaborative leadership. On the other hand, the dominant barriers comprise team hierarchy, workload and time constraints, and misalignment of responsibilities and roles. Additionally, there are gaps in measuring the effectiveness of IPC and a lack of quantitative research to evaluate its impact. Conclusion: Clinical decision-making in complex cases is a challenging process, primarily due to team hierarchy. To overcome these difficulties, an approach that emphasizes enhanced interprofessional communication, strengthened leadership, and patient-centered care is required. By addressing these barriers, the decision-making process can become more effective, ensuring more holistic and patient-centered care.Keywords: Interprofessional collaboration; clinical decision-making; complex cases.